Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have the PDE $$ -\frac{\partial V}{\partial t} + \frac{1}{2}\sigma^2S^2\frac{\partial^2 V}{\partial S^2} + rS\frac{\partial V}{\partial S} - rV = 0$$ with initial and boundary conditions:

  1. $V(0,S)=max(E-S,0) $
  2. $V(t,S^*)=E-S^*(t) $
  3. $V(t,\infty)=0 $

$S^*$ finding from this condition - $\frac{\partial V(t,S)}{\partial S}\bigg|_{S=S^*}=-1$, and for $S\le S^*$ must be performed $\frac{\partial V(t,S)}{\partial t}=0$. Where $\sigma=0.2$, $r=0.08$, $E=100$.

I have to find $V(t,S)$ with $t=0.25$ and $S=100$.

So, I think that this PDE I can solve using finite difference method. Now I did approximation for PDE using forward and backward explicity methods. But I don't know how I can solve boundary condition. What I need to learn for solving this PDE? Or you can solve it, and tell me how you did it. :) Thanx!

share|improve this question
    
Let me try to understand. $S^*$ is an unknown point that can be moving? –  Pragabhava Nov 6 '12 at 4:56
    
I think you're right. It's PDE with free boundary. –  spoluer Nov 6 '12 at 5:21
    
Can you elaborate on the deduction of the model, or provide some reference? –  Pragabhava Nov 6 '12 at 5:27
    
Option Pricing Using The Explicit Finite Difference Method. And C++ in Finance. Last link I used, because I need C++ algorithm for solve this PDE. –  spoluer Nov 6 '12 at 6:40
    
From a quick read, shouldn't the last term $-rS$ be $-rV$? –  Pragabhava Nov 6 '12 at 6:56
show 9 more comments

2 Answers

Although I may have no idea about substitution of the initial and boundary conditions, I have idea of the form of the solution of this PDE, as I able to solve the similar type question.

I think you only interesting about the solution of $t,S\geq0$ :

Let $V(t,S)=F(t)G(S)$

Then $-F'(t)G(S)+\dfrac{1}{2}\sigma^2S^2F(t)G''(S)+rSF(t)G'(S)-rF(t)G(S)=0$

$F'(t)G(S)=\dfrac{\sigma^2F(t)}{2}\left(S^2G''(S)+\dfrac{2r}{\sigma^2}SG'(S)-\dfrac{2r}{\sigma^2}G(S)\right)$

$\dfrac{2F'(t)}{\sigma^2F(t)}=\dfrac{S^2G''(S)+\dfrac{2r}{\sigma^2}SG'(S)-\dfrac{2r}{\sigma^2}G(S)}{G(S)}=-\xi^2-\dfrac{1}{4}\left(\dfrac{2r}{\sigma^2}-1\right)^2-\dfrac{2r}{\sigma^2}$

$\begin{cases}\dfrac{F'(t)}{F(t)}=-\dfrac{\sigma^2\xi^2}{2}-\dfrac{\sigma^2}{8}\left(\dfrac{2r}{\sigma^2}-1\right)^2-r\\S^2G''(S)+\dfrac{2r}{\sigma^2}SG'(S)+\biggl(\xi^2+\dfrac{1}{4}\left(\dfrac{2r}{\sigma^2}-1\right)^2\biggr)G(S)=0\end{cases}$

$\begin{cases}F(t)=c_3(\xi)e^{-t\Bigl(\frac{\sigma^2\xi^2}{2}+\frac{\sigma^2}{8}\bigl(\frac{2r}{\sigma^2}-1\bigr)^2+r\Bigr)}\\G(S)=\begin{cases}c_1(\xi)S^{\frac{1}{2}-\frac{r}{\sigma^2}}\sin(\xi\ln S)+c_2(\xi)S^{\frac{1}{2}-\frac{r}{\sigma^2}}\cos(\xi\ln S)&\text{when}~\xi\neq0\\c_1S^{\frac{1}{2}-\frac{r}{\sigma^2}}\ln S+c_2S^{\frac{1}{2}-\frac{r}{\sigma^2}}\text{when}~\xi=0\end{cases}\end{cases}$

$\therefore V(t,S)=C_1e^{-\Bigl(\frac{\sigma^2}{8}\bigl(\frac{2r}{\sigma^2}-1\bigr)^2+r\Bigr)t}S^{\frac{1}{2}-\frac{r}{\sigma^2}}\ln S+C_2e^{-\Bigl(\frac{\sigma^2}{8}\bigl(\frac{2r}{\sigma^2}-1\bigr)^2+r\Bigr)t}S^{\frac{1}{2}-\frac{r}{\sigma^2}}+\int_0^\infty C_3(\xi)e^{-t\Bigl(\frac{\sigma^2\xi^2}{2}+\frac{\sigma^2}{8}\bigl(\frac{2r}{\sigma^2}-1\bigr)^2+r\Bigr)}S^{\frac{1}{2}-\frac{r}{\sigma^2}}\sin(\xi\ln S)~d\xi+\int_0^\infty C_4(\xi)e^{-t\Bigl(\frac{\sigma^2\xi^2}{2}+\frac{\sigma^2}{8}\bigl(\frac{2r}{\sigma^2}-1\bigr)^2+r\Bigr)}S^{\frac{1}{2}-\frac{r}{\sigma^2}}\cos(\xi\ln S)~d\xi$

share|improve this answer
add comment

I try to calculate ODE in answer from @Pragabhava, but I think I have a mistake in my solution.
For $S=S^*$, $V'(S)=-1$, then $V(S)=-S$ and $V''(S)=0$. To find a general solution I use Liouville's formula.
$\begin{vmatrix} -S & V \\ -1 & V' \\ \end{vmatrix} = ce^{-\int P(S)dS}$
$\int{P(S)dS=\int{\frac{rS}{\frac{1}{2}\sigma^2S^2}}dS}=2\frac{r}{\sigma^2}\int{\frac{dS}{S}}=2\frac{r}{\sigma^2}ln|S|$
$-SV'+V=ce^{-2\frac{r}{\sigma^2}ln|S|}=\frac{c}{S^{2\frac{r}{\sigma^2}}}$
Then I divided by $V^2(S)=S^2$,
$\frac{SV'-V}{S^2}=-\frac{c}{S^{2(\frac{r}{\sigma^2}+1)}}$;
$\big(\frac{V}{S}\big)'=-\frac{c}{S^{2(\frac{r}{\sigma^2}+1)}}$;
$\frac{V}{S}=-c\int\frac{dS}{S^{2(\frac{r}{\sigma^2}+1)}}=c\frac{1}{(2\frac{r}{\sigma^2}+1)S^{(2\frac{r}{\sigma^2}+1)}}$;
$V(S)=\frac{c}{(2\frac{r}{\sigma^2}+1)S^{2(\frac{r}{\sigma^2}+1)}}$
From this common solution I determine $S$:
$-S=\frac{c}{(2\frac{r}{\sigma^2}+1)S^{2(\frac{r}{\sigma^2}+1)}}$;
$S^{2\frac{r}{\sigma^2}+3}=-\frac{c}{2\frac{r}{\sigma^2}+1}$;
$S=\sqrt[2\frac{r}{\sigma^2}+3]{-\frac{c}{2\frac{r}{\sigma^2}+1}}$
Am I right?

share|improve this answer
    
Why dont you use the ansat $V(S) = S^\alpha$ and see what happens with $\alpha$? –  Pragabhava Nov 8 '12 at 4:41
    
Sorry, I don't understand. What does you mean? –  spoluer Nov 8 '12 at 6:41
    
If $V(S) = S^\alpha$, then substituting in the time independent equation leads to $$\left(\frac{1}{2}\sigma^2\alpha + r \right)(\alpha - 1) = 0.$$ Either $\alpha = 1$ or $\alpha = -\frac{2 r}{\sigma^2}$. –  Pragabhava Nov 8 '12 at 6:57
    
Ok, I understand you. But how can you find $S^*(t)$ using this solution? –  spoluer Nov 8 '12 at 7:12
    
I'm not entirely sure, but I would use $V(S) = A S + B S^{-\frac{2 r}{\sigma^2}}$ and evaluate the condition $V(0,S)$, then determine $S^*$ with the condition $\frac{\partial V(S^*)}{\partial S} = 1$, and then do either separation of variables, Laplace transform, or finite differences, whatever works best. –  Pragabhava Nov 8 '12 at 7:17
show 1 more comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.